Physical Activity and Other Strategies in Treatment of Buerger’s Disease - a Systematic Review - Kaczmarek, Julia; Błażuk, Michał; Barczyńska, Katarzyna; Ejsner, Rafał; Grelowska, Aleksandra; Ołubiec, Adrian; Oto, Aleksandra; Poznańska, Nela; Sys, Tomasz (Quality in Sport, 2026)
Buerger’s disease, also known as Thromboangitis obliterans (TAO), is a nonatherosclerotic vascular disorder of unknown etiology, causing distal arterial occlusions. Implication of changes in the vessels is decreased blood flow and ischemia as the result. Buerger’s disease is entirely associated with smoking. Diagnosis of TAO is challenging. Multiple diagnostic criteria have been suggested in the past years. Therefore it is advisable to base diagnosis on unified Delphi criteria. Patients suffering from TAO may present pain in digits as an early symptom, whereas late symptoms may include ulcers, gangrene and intermittent claudication. Current management of TAO lacks standard guidelines. There is no one satisfying strategy, which can be implemented in every single patient. Various conservative and surgical methods might be performed. Each one has its own advantages and disadvantages. To this very day, tobacco cessation is the cornerstone of the treatment. Important, although frequently neglected aspect is an exercise therapy. Modern, satisfying treatment methods are constantly explored.